2014
DOI: 10.1016/j.jor.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Hip fractures in extremely old patients

Abstract: ElderlyHip fracture Mortality Comorbidity a b s t r a c t Aims: The purpose of this study was to report a less seen age-group (>90) of hip fractures and to assess the predictors of functional loss, complications and mortality.Methods: Thirty-two patients at a mean age of 92.8 (±2.7) were treated in a single institution and reported at a mean follow-up of 2.02 (±1.35) years. Conclusion: Hip fractures are challenging in extremely old patients and associated with increased mortality and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…Kapicioglu et al [7] reported a 1-year mortality of 28% (9/32 patients) in a patient population similar to our study. However, in that consecutive follow-up study, all of the patients were excluded or not included if it was not possible to contact them via telephone for a follow-up interview.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Kapicioglu et al [7] reported a 1-year mortality of 28% (9/32 patients) in a patient population similar to our study. However, in that consecutive follow-up study, all of the patients were excluded or not included if it was not possible to contact them via telephone for a follow-up interview.…”
Section: Discussionsupporting
confidence: 91%
“…Our patient population had a mean age of 92 years, which is a parameter that makes our study difficult to compare with many other studies that have also focused on patients of older age [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although results in the literature are similar to our results, [18,19] several publications reported a higher mortality rate in the arthroplasty group. [20] There are several limitations to this study. The follow-up period was short because of the short life expectancy after fracture.…”
Section: Discussionmentioning
confidence: 94%
“…[22] glu et al who have reported higher mortality rates for arthroplasty group than internal fixation. [23,24] On the contrary, other studies found no difference in mortality between internal fixation and arthroplasty. [25,26] There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 95%